Draft Genome Sequence of a Drug-Susceptible New Zealand Isolate of Mycobacterium tuberculosis Lineage 3. - Mac Aogin, Michel; O'Toole, Ronan (My University, 2014)
Multidrug resistance constitutes a threat worldwide to the management of tuberculosis (TB). We report the draft whole-genome sequence of a lineage 3 (East-African Indian) isolate of Mycobacterium tuberculosis which presented as multidrug resistant in New Zealand, and describe a number of single-nucleotide polymorphisms in genes relating to drug resistance.
PUBLISHED
Keywords: tuberculosis (TB); Immunology, Inflammation & Infection; ANTIMICROBIAL RESISTANCE; Microbial genomics; Pathogen genomics